2007
DOI: 10.1677/erc-07-0065
|View full text |Cite
|
Sign up to set email alerts
|

Human adiponectin inhibits cell growth and induces apoptosis in human endometrial carcinoma cells, HEC-1-A and RL95–2

Abstract: Obesity is one of the well-established risk factors for endometrial cancer. Recent clinical studies have demonstrated that circulating adiponectin concentrations are inversely correlated with the incidence of endometrial carcinoma. Such epidemiological findings are consistent with the paradoxical observations that adiponectin levels are reduced in obesity. This study investigated the direct effects of adiponectin on two endometrial carcinoma cell lines, HEC-1-A and RL95-2. These cell lines express both variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 35 publications
4
69
0
2
Order By: Relevance
“…The mechanisms are not clear yet and require further investigation. However, recent studies have provided evidence that adipose tissue can produce many cytokines (adipokines), such as leptin and adiponectin, which can potently affect the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50]. Our data support the hypothesis that these adipose tissue-derived factors are differently associated with the caricinogenesis or progression of GC of each histological type.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mechanisms are not clear yet and require further investigation. However, recent studies have provided evidence that adipose tissue can produce many cytokines (adipokines), such as leptin and adiponectin, which can potently affect the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50]. Our data support the hypothesis that these adipose tissue-derived factors are differently associated with the caricinogenesis or progression of GC of each histological type.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have demonstrated that adipocytes produce a variety of secretory peptides, named adipokines [39,40]. More recently, some adipokines, such as leptin and adiponectin, have been shown to critically regulate the biological behavior of malignant cells [41][42][43][44][45][46][47][48][49][50], raising the possibility that adipocytes may have positive roles in the development of malignant diseases through the secretion of adipokines in an endocrine or intracrine manner. In addition, it has been suggested that the biochemical characteristics of visceral and subcutaneous adipose tissues are somewhat different [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been great interest in determining whether adiponectin has a protective role in carcinogenesis (Kelesidis et al 2006;Byeon et al 2010). Adiponectin has anti-angiogenic (Molica et al 2009), anti-proliferative (Dos Santos et al 2008;Benaitreau et al 2009), and proapoptotic effects, and also arrests cancer cell growth (Kang et al 2005;Cong et al 2007), having both direct effects on carcinogenesis and indirect effects through alteration of hor-mones and cytokine levels (Kelesidis et al 2006).…”
mentioning
confidence: 99%
“…Serum levels of adiponectin have an inverse correlation with BMI and epidemiologic and preclinical data suggest a protective effect for increased adiponectin levels on obesity-related cancer risk [64][65][66][67].…”
Section: Circulating Adipokinesmentioning
confidence: 99%